Poetry in the light of Islamic law : الشعر في ضوء الشريعة الإسلامية - Bano, Dr. Najma; Bano, Saeeda (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Poetry is one of the oldest, most prestigious arts therefore there have been countless poets, critics and researchers on poetry across history, Arabic poetry has played a vital role in the Arabic culture and heritage, it has also passed by many changes throughout history until it reached in the form we see today, in this article we searched about the relation of Arabic poetry with the Islamic law and the influence it has on it as well as the part it plays in it, it is also a response to those who see poetry as a lost and dark art. However, the poetry concerned with the Islamic law has always been honest and pure and has been a tool to explain, express and teach.